Melatonin ameliorates low‐grade inflammation and oxidative stress in young Zucker diabetic fatty rats. Issue 4 (29th September 2012) - Agil, Ahmad; Reiter, Russel J.; Jiménez‐Aranda, Aroa; Ibán‐Arias, Ruth; Navarro‐Alarcón, Miguel; Marchal, Juan Antonio; Adem, Abdu; Fernández‐Vázquez, Gumersindo
Abstract: The aim of this study was to investigate the effects of melatonin on low‐grade inflammation and oxidative stress in young male Zucker diabetic fatty (ZDF) rats, an experimental model of metabolic syndrome and type 2 diabetes mellitus (T2DM). ZDF rats (n = 30) and lean littermates (ZL) (n = 30) were used. At 6 wk of age, both lean and fatty animals were subdivided into three groups, each composed of 10 rats: naive (N), vehicle treated (V), and melatonin treated (M) (10 mg/kg/day) for 6 wk. Vehicle and melatonin were added to the drinking water. Pro‐inflammatory state was evaluated by plasma levels of interleukin‐6 (IL‐6), tumor necrosis factor‐α (TNF‐α), and C‐reactive protein (CRP). Also, oxidative stress was assessed by plasma lipid peroxidation (LPO), both basal and after Fe 2+ /H2 O2 inducement. ZDF rats exhibited higher levels of IL‐6 (112.4 ± 1.5 pg/mL), TNF‐α (11.0 ± 0.1 pg/mL) and CRP (828 ± 16.0 µg/mL) compared with lean rats (IL‐6, 89.9 ± 1.0, P  <   0.01; TNF‐α, 9.7 ± 0.4, P  <   0.01; CRP, 508 ± 21.5, P  <   0.001). Melatonin lowered IL‐6 (10%, P  <   0.05), TNF‐α (10%, P  <   0.05), and CRP (21%, P  <   0.01). Basal and Fe 2+ /H2 O2 ‐induced LPO, expressed as malondialdehyde equivalents (µmol/L), were higher in ZDF rats (basal, 3.2 ± 0.1 versus 2.5 ± 0.1 in ZL, P  <   0.01; Fe 2+ /H2 O2 ‐induced, 8.7 ± 0.2 versus 5.5 ± 0.3 in ZL; P  <   0.001). Melatonin improved basal LPO (15%, P  <   0.05) in ZDF rats, and Fe 2+ /H2 O2 ‐ induced LPO in both ZL (15.2%, P  <   0.01) and ZDF rats (39%, P  <   0.001). These results demonstrated that oral melatonin administration ameliorates the pro‐inflammatory state and oxidative stress, which underlie the development of insulin resistance and their consequences, metabolic syndrome, diabetes, and cardiovascular disease.